2017
DOI: 10.4172/2329-9096.1000386
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost 2-Channel Electromyography Telemeter using a Personal Computer Microphone Port

Abstract: Objective: For the convenient use of electromyography devices in physical rehabilitation during locomotion, we developed a simple, low-cost 2-channel electromyography telemeter (LC-EMGT) that can be connected wirelessly with a personal computer (PC) microphone port.The aim of this study was to verify whether the performance of our LC-EMGT fulfills the need for monitoring EMG during locomotion of patients in rehabilitation. For this purpose, we compared the performance of our LC-EMGT with an existing EMG device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The control of the virtual and prosthetic hand is performed using a microcontroller or computer and data acquisition card, according to the design approach. The commercial prosthetic hand setup consists of single-channel, single threshold level and a servo motor (Suzuki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The control of the virtual and prosthetic hand is performed using a microcontroller or computer and data acquisition card, according to the design approach. The commercial prosthetic hand setup consists of single-channel, single threshold level and a servo motor (Suzuki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the possibility to create low-cost and efficient SEMG data acquisition systems (consisting of an amplifier and wireless transmitter) for only [ 8 ], which is already more affordable than commercial solutions. However, this price does not include the cost of electrodes, which can add a significant increase in cost.…”
Section: Introductionmentioning
confidence: 99%